Weighted ergodic theorems for Banach–Kantorovich lattice Lp(∇ ,μ) - Mukhamedov, Farrukh; Ganiev, Inomjon (Springer, 2013)
In the present paper we prove weighted ergodic theorems and multiparameter weighted ergodic theorems for positive contractions acting on Lp(∇,μ). Our main tool is the use of methods of measurable bundles of Banach–Kantorovich lattices.